Intervensi Keperawatan Dalam Upaya Peningkatan Keefektifan Pola Nafas Pada Pasien Chf - Lisanul Jannah, Meiriza, Enita Dewi , S.Kep.,Ns.,M.N (2017)
ABSTRACT Background the main causes of CHF are elderly people suffering from hypertension, heart valve due to calcification. health problems with cardiovascular system disorders including CHF is still ranked high, CHF has involved 23 million people in the world. Objective writing a scientific paper aims to assess the problem of nursing at the ineffectiveness of breathing patterns that emerged in CHF disease and report that back breathing pattern effectively. Methode in this paper the authors report uses the case study method using the nursing process approach include interviews, observation, and documentation taken from a nursing notes. Authors can understand nursing care in patients with CHF through one of the wards in hospitals. Results the authors conclude nursing diagnoses for patients with the ineffectiveness of breathing patterns associated with respiratory muscle fatigue. By doing nursing care with the implementation of an increase in oxygen delivery, respiratory monitoring, and positioning the head 45 is higher than the body / semi-Fowler. Discussion and Conclusions the problem of nursing with the ineffectiveness of breathing patterns associated with respiratory muscle fatigue can be overcome in part so that the need to continue the intervention by positioning the semi-Fowler's head, increased oxygen, and administration of analgesic drugs to obtain outcomes that will be achieved. Semi-Fowler's position to reduce shortness of breath due to their gravity.